Analysis of Teachers' Understanding of the Flipped Classroom Model and its Implementation in Schools through The Rasch Model Approach - Riskawati Riskawati; Khaeruddin Khaeruddin; Riska Amanda Putri; Karnila Karnila; Aulia Rahman; Cindy Salsabila (Pustaka Digital Indonesia, 2025)
The integration of technology in education has become increasingly essential for enhancing the quality of learning in the digital era. One innovative instructional model that has gained significant attention is the Flipped Classroom, in which active learning occurs outside the classroom through videos, readings, or other preparatory activities, while face-to-face class time is dedicated to discussion, problem-solving, and practical application of knowledge. Despite its potential, the implementation of this model often faces several challenges, particularly regarding teachers’ readiness, availability of infrastructure, and their technological competencies. In Makassar City, limited empirical studies have been conducted to examine the level of teachers’ understanding of the Flipped Classroom and the obstacles they experience in applying it in schools. Insufficient comprehension of the model among teachers may reduce its effectiveness and, consequently, negatively impact the overall quality of technology-based learning. Understanding these challenges is therefore critical to inform professional development, curriculum planning, and institutional support strategies. This study aims to analyze teachers’ knowledge of the Flipped Classroom model and identify key implementation barriers, providing an empirical foundation to optimize technology-driven instructional practices in secondary education.